2021
DOI: 10.1037/emo0001006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive appraisal contributes to feeling generation through emotional evidence accumulation rate: Evidence from instructed fictional reappraisal.

Abstract: How do (reportable) emotional feelings come to be? Following William James and many others, Givon et al. ( 2020) described the generation of feelings as evidence accumulation toward a boundary. In this work, we began clarifying the nature of "evidence". In two preregistered experiments, participants were presented with normed emotion-evoking negative/positive pictures that were described as reflecting either authentic or fictitious happenings ("fictional reappraisal"). In negative pictures (but contrary to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Likewise, when we become aware of our emotions, our consciousness apparatus collects neural evidence from the interoceptive apparatus, from our sensation of action tendencies, from cognitions, and so forth. As shown here, and following other works from our group (Givon et al, 2020, 2022; Singer-Landau & Meiran, 2021), this evidence accumulation process is very well described by the LBA and, as shown here, roughly equally so for “usual” perception and for emotional feelings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, when we become aware of our emotions, our consciousness apparatus collects neural evidence from the interoceptive apparatus, from our sensation of action tendencies, from cognitions, and so forth. As shown here, and following other works from our group (Givon et al, 2020, 2022; Singer-Landau & Meiran, 2021), this evidence accumulation process is very well described by the LBA and, as shown here, roughly equally so for “usual” perception and for emotional feelings.…”
Section: Discussionsupporting
confidence: 90%
“…More information regarding the modeling of the circle task can be found in the online supplemental materials. We may add that the legitimacy of using the LBA to model emotion reports is additionally gained from other studies (Givon et al, 2020;Singer-Landau & Meiran, 2021) where critical components of model validation were included, including comparison to alternative models and showing selective influence of manipulations on the predicted LBA parameters.…”
Section: Pleasant Emotional Feelings Follow Weber's Lawmentioning
confidence: 99%
“…First, we previously found that reappraisal increased the rate of aberrant emotion reports (made in response to negative pictures; Singer-Landau & Meiran, 2021) showing that the aberrations are emotion related. Second, both RT and aberrations were explained by joint modeling, in terms of evidence accumulation (Givon et al, 2020; Singer-Landau & Meiran, 2021). In addition, our modeling provides an explanation for the heavier right RT-distribution tail in aberrant responses.…”
Section: Discussionmentioning
confidence: 95%
“…This enabled them to further show that emotional feelings, thus measured, follow Weber’s Law, which is the most basic law of sensation. Additional works show a selective influence of cognitive appraisals on the drift-rate (Singer-Landau & Meiran, 2021 ) and selective influence of speed-accuracy emphasis on the boundary (Givon et al, 2022 ).…”
Section: The Linear Ballistic Accumulator Modelmentioning
confidence: 99%
“…In a recent series of works (Berkovich & Meiran, 2023 ; Givon et al, 2020 , 2023 ; Singer-Landau & Meiran, 2021 ), our lab used evidence accumulation modeling to describe the emergence of conscious reportable emotional feelings. Our paradigm involves asking participants to report, using a key press, if a stimulus makes them feel pleasant versus unpleasant.…”
Section: Emotional Feelings As Evidence Accumulationmentioning
confidence: 99%